IN VITRO STUDY OF SUPERFICIAL ENAMEL LAYER OF PERMANENT TEETH DURING STAGE OF SECONDARY MINERALIZATION - G.M. Grigorenko; L.A. Khomenko; G.V. Sorochenko; L.M. Kapitanchuk (Український стоматологічний альманах, 2015)
Introduction. The lowest level of mineralization of hard dental tissues is observed during the first year after teeth eruption. This is confirmed by significant increase of prevalence and intensity of caries in permanent teeth from 6 to 15 years. Enamel caries-resistance changes during secondary mineralization. These confirm importance of the study of changes in the properties of the superficial enamel layer of permanent teeth during the period of intensive secondary mineralization.